Participant Retention in a HIV Prevention Cohort Study in Kisumu, Kenya - Nyambura M.; Otieno F.; Ndivo R.; Williamson J.; Pals S.; Mills L.A.; Gust D.A. (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
Retention of sufficient numbers of participants in longitudinal research studies is a serious methodological concern, as retention influences the validity of the research findings. An assessment of participant retention or attending all study visits was made quarterly during a 12 month follow-up of an HIV incident cohort in Kisumu, Kenya. The study objectives were to determine 1) the proportion of participants attending all study visits and 2) demographic and behavioral factors associated with missing ≥ 1 visit. The Kisumu Incidence Cohort Study (KICoS) was initiated in January 2007 (N=831). Detailed contact information was collected from each participant to enhance retention. Bivariate and multivariable analyses were used to determine factors associated with missing ≥ 1 visit. Overall retention was 90%. Of those enrolled, 46.4% were females. The adjusted odds of missing ≥ 1 study visit were greater for participants who were female (AOR=2.85; CI=1.90-4.28) and who had technical training (AOR=2.51; CI=1.20-5.25) or college/university education (AOR=1.89; CI=1.10-3.24) compared to having no or only primary education. Retention was high in this HIV prevention cohort study. However, studies could benefit by tailoring retention strategies for women. Disclaimer: The findings and conclusions in this report are those of the authors and do not necessarily represent the views of their respective institutions.
Keywords: cohort studies